Relentless goodbye : grief and love in the shadow of dementia - Burkholder, Ginnie Horst, 1944- (Harrisonburg, Va. : Herald Press, 2012)
Burkholder reveals how she handles the constant challenges of caring for a spouse who is slowly slipping away to Lewy body dementia. She shows how illness and health, faith and doubt, grief and acceptance all flow together in the river of change.
Includes bibliographical references.
Description based on print version record.
Keywords: Lewy body dementia -- Patients -- Family relationships; Caregivers -- Family relationships; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; Electronic books